Efficacy and Safety of Pregabalin for Fibromyalgia in a Population of Chinese Subjects - Zhang, Xiao (J Pain Res, 2021)
PURPOSE: Fibromyalgia (FM) may go underdiagnosed and untreated in China in part due to a lack of awareness and understanding of the condition, and limited available treatments. PATIENTS AND METHODS: This randomized, double-blind, Phase III local registration trial compared the efficacy and safety of pregabalin (flexibly dosed 300–450 mg/day) versus placebo for the management of pain in Chinese adults diagnosed with FM according to American College of Rheumatology 1990 criteria, across 22 centers within China. Patients reported pain score of ≥40 mm on 100-mm scale (from 0 “no pain” to 100 “worst possible pain”). The primary efficacy endpoint was change from baseline to Week 14 in mean pain score (MPS). Secondary endpoints included measures of sleep and sleep interference. Safety and tolerability were monitored throughout. RESULTS: Median pregabalin dose was 335 mg/day. A significant reduction from baseline to Week 14 in weekly MPS was seen for patients treated with pregabalin (n=170) versus placebo (n=164) (least-squares mean difference [95% confidence interval]: –0.73 [–1.10 to –0.36]; P=0.0001). Significantly greater proportions of patients experienced ≥30% and ≥50% reductions in MPS at Week 14 with pregabalin versus placebo. Pregabalin-treated subjects demonstrated improvements in measures of sleep and sleep interference. Pregabalin was generally well tolerated. The most common adverse events were dizziness and somnolence; no serious adverse events (SAEs) occurred in pregabalin-treated subjects. Nine placebo-treated subjects experienced SAEs. CONCLUSION: Pregabalin (300–450 mg/day) is a safe and effective treatment for reducing pain and improving sleep in native Chinese subjects with FM. CLINICALTRIALS.GOV IDENTIFIER: NCT01387607.